Two new species of the snake eel genus Bascanichthys (Anguilliformes: Ophichthidae) from the northwestern Pacific - Hibino, Yusuke; Yamashita, Kenta; Sakurai, You; Ho, Hsuan-Ching (Zootaxa, 2022)
Two new species of the elongate snake eel genus Bascanichthys are described from the northwestern Pacific. Bascanichthys kabeyawan sp. nov. is described based on a single specimen collected from estuary of southern Taiwan. It is characterized by having head 4.6% TL; tail 52.3% TL; body depth at gill opening 1.1% TL; predorsal-fin length 58.4% HL; snout length 10.9% HL; body bicolored, head without bands; lateral-line pores anterior to anus 104; vertebral formula 4-103-224. Bascanichthys ryukyuensis sp. nov. is described based on two specimens collected from the shallow water of Okinawa-jima Island, Ryukyu Islands of southern Japan. It is characterized by having head 3.7–4.3% TL; tail 43.3–44.2% TL; predorsal-fin length 40.7–45.4% HL; snout length 11.3–13.1% HL; body pale brown, head without distinct dark bands after preservation; lateral-line pores anterior to anus 114–118; total vertebrae 207–216, mean vertebral formula 2-116-212; and dorsal-fin origin before middle of head.